A study of book selection and book censorship practices of children's and fiction collection of selected public libraries in Metro Manila - Neri, Carolyn T.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
Literature plays a vital role in enriching the mind and imagination of an individual. In this light, children are encouraged to be exposed to literature that will teach the child valuable lessons in life and elevate their interest in reading.
Children, are voracious readers (McColvin, 1964). Therefore there is a need for society to give them the proper guidance in choosing the right books for them to read. It is in this light that this study focused on book selection and book censorship practices of three selected public libraries in Metro Manila (Makati City Library, Pasig Discovery Centrum and Library Learning Resource Center, and Quezon City Public Library).
The researcher evaluated the collection of the institutions and compared the titles from the collection against the set of standards (ALA Most Frequently Challenged books and PBBY-NBDB Banned Books) to determine if some materials from the hit lists appear in the collection. After the evaluation, a follow-up interview with the librarian and library officers was conducted.
The evaluation of the collections against the set of standards revealed that of the three subject libraries Makati City Library has the most number of foreign banned titles in their collection. The evaluation of the collection resulted to twelve (9 foreign, 3 Filipiniana) banned titles that are all available for circulation and loan. Pasig Discovery Centrum and Library Learning Resource Center has the most number of banned Filipiniana titles in their collection.
The evaluation of the collection against the hit lists obtained eighteen (4 foreign and 14 Filipiniana) banned titles that the library has acquired already. The foreign titles listed above are available for circulation and loan while the Filipiniana materials are used during storytelling. QCPL has only two banned title in their collection, both are foreign titles. Pasig and QCPL decided to enforce censorship among the banned titles in the collection and in the hit lists, while Makati chose not to take any action against the banned materials in their collection although they admit that they might consult the hit lists next time they procure and acquire new title.
Recommendations included familiarization of Head Librarians and Library Officers with standards set not only by ALA and NBDB but other institutions as well, provision of written Collection Development Policy, advocating intellectual freedom of clientele regardless of age, and rallying support from local government officials and units.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Makati City Library; Pasig Discovery Centrum and Library Learning Resource Center; Quezon City Public Library; Public libraries -- Philippines -- Manila Metropolitan Area